2023
DOI: 10.3390/tropicalmed8100456
|View full text |Cite
|
Sign up to set email alerts
|

Tungiasis: Participation of Cats and Chickens in the Dispersion and Maintenance of the Disease in an Endemic Tourist Area in Brazil

Jamille Bispo de Carvalho Teixeira,
Katharine Costa dos Santos,
Paula Elisa Brandão Guedes
et al.

Abstract: Tunga spp. are fleas commonly found in impoverished tropical regions. In Vila Juerana, a tourist community in Ilheus, Bahia, Brazil, where tungiasis is endemic, dogs are the main host of fleas during their life cycle. However, there is no information about the role of cats and chickens in tungiasis in the village. Of the 272 households investigated, 112 had domestic animals, 48 had only dogs, 28 had only cats, and nine had only chickens. Of the 27 households with cohabitation among species, 16 had cats and dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Most of the village community have precarious sanitary and social conditions. The streets are unpaved and consist of sandy and clay soil, and some buildings are unfinished without concrete floors [ 8 , 25 ]. Moreover, the study area had previously shown a high year-round prevalence of tungiasis in dogs [ 8 , 16 , 23 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Most of the village community have precarious sanitary and social conditions. The streets are unpaved and consist of sandy and clay soil, and some buildings are unfinished without concrete floors [ 8 , 25 ]. Moreover, the study area had previously shown a high year-round prevalence of tungiasis in dogs [ 8 , 16 , 23 26 ].…”
Section: Methodsmentioning
confidence: 99%